STUDENTS’ PERCEPTION TOWARD THEIR SPEAKING ENGLISH ABILITY AFTER BEING TAUGHT THROUGH GOSSIPING GROUP TECHNIQUE AT SMAN 3 BATUSANGKAR - Dian Purnama Sari (STBA Prayoga Padang, 2017)
This research aimed to know X grade students’ of SMA N 3 Batusangkar perception toward their English speaking ability after being taught by using gossiping group technique. This research discussed five aspects of students’ speaking ability toward their comprehension, fluency, vocabulary, pronunciation, and grammar used in speaking. Based on calculation, students’ perception toward their speaking ability after studying English by using gossiping group technique was positive. Students’ perception toward those five aspects is clarified well. So it can be concluded that the students think their English speaking ability is better after being taught by using gossiping group technique. Moreover, it is hoped that there is a good corporation between teacher and students to maximize the use of gossiping group technique to improve students’ speaking English ability.